CollabVR: A Social VR Architecture for Social Interaction Between College Students - Johnson, Diego (2024)
This paper explores the challenges and solutions to the decrease in social interaction in the university environment due to the adoption of online classes. The proposal frames the use of Virtual Reality (VR) for the creation of CollabVR, a social interaction platform. CollabVR is based on a technological architecture oriented towards managing extracurricular activities in VR environments, with the aim of enhancing social interaction among university students. This architecture follows a microservices approach and includes a web application and a VR application. To assess the technological feasibility of CollabVR, a focus group of software architecture experts was organized. The results showed that 66% of them agreed that the proposed architectural diagrams provide a clear and complete representation of the interaction between users, devices, applications, and servers. In addition, 100% of the experts deemed the proposed solution as highly viable. They highlighted that the suggested services and components would contribute to significantly improve students’ social interaction. In summary, the conceptual model of CollabVR provides a space for socialization, paving the way to enhance the remote educational experience and contributing to the social well-being of the students.